ANALISIS NILAI TAMBAH DAN STRATEGI PENGEMBANGAN HOME INDUSTRY KUPANG KERING DI DESA BALONGDOWO KECAMATAN CANDI KABUPATEN SIDOARJO - Ari Wahyu Diarsa; Jani Januar; Anik Suwandari (University of Jember, 2017)
Shellfish is the raw material for making dried shellfish. Home industry located in Balongdowo village, Sidoarjo regency has long been cultivated, but until now most of the craftsmen have not showed significant development. This study was aimed to determine value added of shellfish based product dried, cost efficiency of dried shellfish processed product, and development strategy at dried shellfish home industry in Balongdowo Village, Sidoarjo Regency. Analyzer used include analysis of value added, analysis efficiency cost, and SWOT analysis. The result of the analysis shows that: (1) Wet shellfish added value in shellfish dried home industries medium, (2) Home industry shellfish dried in the use of production cost has been efficient, (3) The appropriate development strategy to be applied was using the W-O strategy that was by dried shellfish industry should use labour maximization, good packaging process, labelling, and try to get healt-assesment certification to expand the marketing process.